Cobalt Complexes as Antiviral and Antibacterial Agents - Eddie L. Chang; Christa Simmers; D. Andrew Knight (MDPI AG, 2010)
Metal ion complexes are playing an increasing role in the development of antimicrobials. We review here the antimicrobial properties of cobalt coordination complexes in oxidation state 3+. In addition to reviewing the cobalt complexes containing polydentate donor ligands, we also focus on the antimicrobial activity of the homoleptic [Co(NH3)6]3+ ion.